Preservation Of Illocutionary And Perlocutionary Effects Of Jokes In Translation - Rustamov Ilkhom Tursunovich (Open Academia, 2025)
This article explores the preservation of illocutionary and perlocutionary effects of jokes in the translation process. Based on a pragmalinguistic approach, it analyzes the recreation of speech acts in translation, strategies for ensuring pragmatic effectiveness of humorous texts in intercultural communication, and transformation of language games. The linguistic and cultural competencies necessary for proper understanding of illocutionary intent and its recreation through appropriate means, as well as preservation of perlocutionary effect in joke translation, are discussed. The article examines the illocutionary and perlocutionary characteristics of jokes, their connection with cultural codes, and practical aspects of pragmatic adaptation using examples from Uzbek and English languages
Keywords: Pragmalinguistics; speech act; illocution; perlocution